Factors hindering the development of programmes for children with learning disabilities in Lagos state, Nigeria (2015)
Prevalent problems hindering the development of Services for children with learning disabilities in Lagos State, Nigeria necessitated this study. Random sampling technique was used in the selection of 226participants that comprised teachers and offìcials of the Ministry of Education in a general survey design. A 14-item questionnaire was the major instrument used in eliciting responses from the participants about factors that hinder the development of learning disabilities programmes. The data was analysed with descriptive statistics. The result showed that three factors namely; unqualifìed teachers, lack of motivation or incentives for teachers of children with learning disabilities, and scanty monitoring of special education programmes with item mean ratings of 4.62, 4.54 and 4.51 respectively, exerted the greatest negative influence towards the development of programmes for children with learning disabilities in Lagos State. Recommendations for successful development and implementation of programmes for children with learning disabilities were highlighted.